(untitled) (Research, Society and Development, 2022)
Objective: To verify the accuracy of functional tests in identifying frail older adults in two different regions. Methods: Observational, descriptive and cross-sectional study with the participation of 120 community older adults. Fried Phenotype and Edmonton Frail Scale were used to classify the frailty and the Timed Up and Go (TUG) and gait speed tests to identify the frail older adults. Results: In Ribeirão Preto and Lagarto, frail older adults performed TUG test in a longer time than pre-frail (p = 0.001) and non-frail (p < 0.001). As for gait speed, frail older adults had lower speed than non-frail (p = 0.01). The TUG test had moderate accuracy for the identification of frail older adults in Ribeirão Preto (AUC = 0.86, 95% CI 0.78 to 0.95, p < 0.001) and in Lagarto (AUC = 0.76, 95% CI 0.64 to 0.88, p = 0.001). Gait speed, on the other hand, is not accurate to discriminate frail older adults. The cut-off points for TUG with the highest sensitivity and specificity were 11.5 seconds for both older adults living in Ribeirão Preto and Lagarto. Conclusion: The TUG was capable of identifying frail older adults of two different regions, even when two different diagnostic methods of frailty were applied, standing out as a simple screening to be used in clinical practice.